A systematic video analysis of 21 anterior cruciate ligament injuries in elite netball players during games - Belcher, S.; Whatman, C.; Brughelli, M. (Sports Biomechanics, 2022)
This systematic video analysis of 21 anterior cruciate ligament (ACL) injuries sustained by elite-level netball players during televised games, describes the situation, movement pattern and player behaviour, providing insight regarding the injury mechanism. Seventeen of the ACL injuries occurred from jump-landing actions and only two from cutting manoeuvres. A common scenario was identified for 11 players. In this scenario, players were decelerating rapidly after jumping to receive a high pass, utilising a double-footed landing with a wide base of support (WBOS). Deceleration appeared to be applied predominantly via the injured leg with the knee extended and foot planted. Often the players appeared unbalanced on landing leaning too far back. ACL injury risk was possibly exacerbated by the players head turning away from the injured side. A further compressive knee moment may have been placed on the lateral aspect of the knee by bringing the ball from a high position to a low position at the estimated time of injury. Players may benefit from landing technique training programmes that encourage shoulder-width foot landings, with =30° knee flexion, a small amount of plantar-flexion and good balance. Incorporating challenges to players balance and ability to cope with perturbations may also be beneficial. Training programmes should include instruction on securing the ball in a stable above pelvis-level position after receiving a pass and bringing their whole body around during landing into the direction of their next pass, rather than simply turning their head to look.